INFORMATION SYSTEM STRATEGIC PLANNING WITH ENTERPRISE ARCHITECTURE PLANNING - Astri, Lola Yorita; Gaol, Ford Lumban (CommIT (Communication and Information Technology) Journal, 2013)
An integrated information system is needed in an enterprise to support businessprocesses run by an enterprise. Therefore, to develop information system can use enterprisearchitecture approach which can define strategic planning of enterprise information system. SMPNegeri 1 Jambi can be viewed as an enterprise because there are entities that should be managedthrough an integrated information system. Since there has been no unification of different elementsin a unity yet, enterprise architecture model using Enterprise Architecture Planning (EAP) isneeded which will obtain strategic planning of enterprise information system in SMP Negeri 1Jambi. The goal of strategic planning of information system with Enterprise Architecture Planning(EAP) is to define primary activities run by SMP Negeri 1 Jambi and support activities supportingprimary activities. They can be used as a basis for making data architecture which is the entities ofapplication architecture. At last, technology architecture is designed to describe technology neededto provide environment for data application. The plan of implementation is the activity plan madeto implemented architectures by enterprise.